Age-Stratified Reference Ranges for Directly Measured Serum Free Testosterone in Community-Dwelling and Healthy Men - Walravens, Joeri; Snaterse, Gido; Narinx, Nick; Reyns, Tim; Van Uytfanghe, Katleen; Vanderschueren, Dirk; Wu, Frederick; Kaufman, Jean-Marc; Antonio, Leen; Fiers, Tom; Lapauw, Bruno (The journal of clinical endocrinology and metabolism, 2025)
Direct measurement of serum free testosterone (FT) may help evaluate hypogonadism in men. However, up to present, availability of reference ranges for measured FT (mFT) is limited. To establish age-stratified reference ranges for mFT in healthy and community-dwelling adult men. Serum samples of 1202 Caucasian men were collected from large population cohort studies. Free testosterone was measured using equilibrium dialysis followed by liquid chromatography tandem-mass spectrometry (LC-MS/MS). Sex-hormone binding globulin was measured using immunoassay and total testosterone was measured using LC-MS/MS. Reference ranges per age decade and for men aged 18 to 39 years with BMI < 30 kg/m² were established following Clinical & Laboratory Standards Institute guidelines. Reference ranges were established as the 2.5th and 97.5th percentiles. The reference range for mFT in healthy, non-obese men aged 18 to 39 years was 184-749 pmol/L. mFT levels showed a decrease with aging of -4.5 pmol/L per year. Having a BMI of 30 kg/m² and 35 kg/m² resulted in a decrease in mFT of 14.4% and 22.2%, respectively, compared to a reference BMI of 22 kg/m². This study provides age-stratified reference ranges for mFT in adult men, established in the largest cohort to date, using published methodology. Our results also show that mFT levels are influenced by age and BMI. Future work should focus on whether age-stratified or reference ranges for young men should be employed, and how mFT can best be implemented in clinical practice including the improved application of calculated FT.